Straight into the Eyes – Jacek Łumiński and the Silesian Dance Theatre(1991-2011) - IWANSKA, ALICJA (Journal of Education Culture and Society, 2020)
The fi nal decade of the 20th century was the turning-point for the development of Polish contemporary dance. In 1991 Jacek Łumiński established the Silesian Dance Theatre in Bytom. The theatre is said to be in the avant-garde of all activities related to contemporary dance development in Poland. It was J. Łumiński and his theatre who pioneered new trends in contemporary dance at the beginning of the nineties of the 20th century, at the same time they have conducted educational activity over the intervening twenty years.The aim of this article is to present the artistic and educational activity of the Silesian Dance Theatre of the recent twenty years. In the beginning the author presents a choreographic por-trait of J. Łumiński, the founder and choreographer of the Silesian Dance Theatre, and creator of the Polish contemporary dance technique. Then an analysis of J. Łumiński’s dance style is car-ried out, and the review of the Silesian Dance Theatre’s choreographic attainments is presented.The fi nal part of the article discusses the wide spectrum of educational activities under-taken in the fi eld of contemporary professional dance by theSilesian Dance Theatre, and the phenomenon of the theatre on the Polish stage.